Open splenic artery aneurysm repair in a patient with previous laparoscopic sleeve gastrectomy. Issue 11 (24th November 2022) - Smith, Sonya Ann; Auld, Michael; Ogg, Murray; Chandrasegaram, Manju Dashini
Abstract : We present the case of a female patient in her 40s who underwent a splenic artery aneurysm (SAA) repair following a previous laparoscopic sleeve gastrectomy (SG). We aim to discuss the management approach to SAAs and considerations in the setting of previous bariatric surgery. The patient consented to this case report. We include preoperative and postoperative radiological images and intraoperative images. While pseudoaneurysms following bariatric surgery have been reported, we present a case of a likely true SAA following SG. Our experience may assist others who come across similar cases in the future.